Large Vestibular Aqueduct Syndrome Causing Progressive Hearing Loss in Childhood Article - Salman Baig; Sana Ansari; Nash Patel; Nial Considine (ziauddin University, 2024)
Background: Sensorineural hearing loss in adults is commonly associated with aging, trauma or autoimmune disease. In children, however, sensorineural hearing loss can also be due to genetic causes, leading to malformation of internal ear structures, like the vestibular aqueduct. In this article we present a rare anatomic malformation which causes progressive hearing loss in children. Methods: Our patient is a 12 year old boy who presented with deafness and tinnitus after mild trauma to the side of the head. Steroids and carbogen were administered but showed no improvement. Results: Audiological evaluation demonstrated profound bilateral sensorineural hearing loss. Radiological investigations including CT scan and MRI of the temporal bone showed bilateral enlargement of the vestibular aqueduct. Conclusion: The patient was diagnosed with Large Vestibular Aqueduct Syndrome and recommended cochlear implantation which has a high success rate and improves the quality of life for the patient. Key Words: Sensorineural hearing loss, Enlarged vestibular aqueduct, enlargedvestibular aqueduct syndrome.